Measuring the quality of sustainability disclosure among the Malaysian commercial banks - Harun N.A.; Rashid A.A.; Alrazi B. (2023)
The banking industry in Malaysia is undergoing fundamental changes due to a number of factors such as market liberalism, stakeholder expectation and environmental risks.In recent years, competitive and regulatory landscapes in the financial services industry have been evolving at an unprecedented speed. Moving forward, organizations in the industry must seek ways to improve profitability while balancing the demands from regulators and other stakeholders. In this regard, sustainability disclosure is seen as a medium that can be used in conveying the necessary information. However, in the absence of any standard guidelines available for banking institutions particularly in Malaysia, the sustainability information reported by the banks is less comparable and thus its quality is relatively unknown. In this study,we employed content analysis in order to measure the quality of sustainability disclosure by 15 commercial banks in Malaysia. In doing so, we have developed a disclosure index based on the Global Reporting Initiatives (G3.1) guidelines. With the development of the disclosure index, it enables benchmarking the sustainability disclosure across the banks and is expected to increase the transparency and standardization in disclosure in the future. IDOSI Publications, 2013.